Hubungan antara Asesmen Kompetensi Minimum dan Kemampuan Berpikir Tingkat Tinggi pada Pembelajaran Matematika Siswa Kelas V SDN Jember Lor 03 - Utama, Refana Widya; Masyhud, M. Sulthon; Alfarisi, Ridho (Universitas Negeri Surabaya, 2024)
This research is correlational research with product moment correlation analysis. This research uses quantitative methods using test instruments and documentation data from AKM simulation results. The aim of this research is to determine whether or not there is a relationship between the Minimum Competency Assessment and Higher Level Thinking Skills in Mathematics Learning for Class V Students at SDN Jember Lor 03. The research was carried out at SDN Jember Lor 03, Jember Regency. The subjects of this research were 82 class V students. The data analysis technique used was product moment correlation analysis. The correlation coefficient result is 0.478 which is greater than the r-table value of 0.213 so that the research results show that there is a positive and significant relationship between the minimum competency assessment and high-level thinking abilities in class V students and the results. The resulting determinant coefficient is 23%, meaning that the minimum competency assessment variable influences high-level thinking abilities by 23% and the remainder comes from other factors in the form of internal factors, namely the level of intelligence, intelligence, attention, interest, talent, motivation and readiness of students, external factors that influence including teaching methods, teacher and student relations, school programs and teaching facilities